Discourses of compassion from the margins of healthcare: perspectives of mental health nurses and patients with lived experience of mental health care - Bond, Carmel (2023)
UK healthcare policy has observed over a decade of changes that have arisen from a discourse of compassion as a marker for high-quality experiences of care. However, at the time of writing this thesis, there is little empirical work that has attempted to describe the political influences on the contemporary conceptualisation of compassion and how those influences might have shaped how compassion is understood in healthcare. In addition, despite a growing body of global research on compassion, the practical setting of mental health is largely absent. This thesis sought to address these gaps by using a critical lens to explore compassion and to examine how it is discursively constructed in relation to power, institutions, and social practices. This study adopted a critical discourse method to examine various dimensions of discourse, at multiple social strata. Conducted in three phases, it encompassed data arising from a document analysis (political and organisational discourse), interviews with mental health nurses (n=7), and interviews with patients (n=10). Results were compared to the existing literature and to the chosen theoretical concepts to offer insight into how the data confirmed, contradicted, or expanded current knowledge. Findings revealed how compassion had been presented as a way of having solved the problem of a perceived compassion deficit in nursing, with political strategies described in detail that were implicated in having made the solution (compassionate care) capable of being realised. Both mental health nurses and patients constructed compassion as an innate ‘natural’ trait. Mental health nurses resisted state regulation of compassion in their practice, arguing instead that they were the embodiment of compassion. Although compassion was considered essential for mental health and the recovery process, unseen forces in the social world inhibited compassion. For instance, the structure of mental health services made it difficult for patients to access care. Medical discourses were shown to dominate the discipline and practice of psychiatry, which were theorised to have influenced individual and group systems of attitudes, beliefs, and values such that discourses of compassion and humanistic approaches were marginalised. Hence, the implicit value and function of compassion to positively impact health and wellbeing was easily overlooked.